2022
DOI: 10.3389/fimmu.2022.917497
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Molecular Regulation Mechanisms of Salinity Stress on the Health and Disease Resistance of Grass Carp

Abstract: Though some freshwater fish have been successfully cultivated in saline-alkali water, the survival rates of freshwater fish are greatly affected by different saline-alkali conditions. The mechanisms of immune adaptation or immunosuppression of freshwater fish under different saline-alkali stress remain unclear. Here, grass carp were exposed to 3‰ and 6‰ salinity for 30 days. It was observed that salinity treatments had no obvious effects on survival rates, but significantly increased the percent of unhealthy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…NLRs play a crucial role in the inflammatory response by forming an inflammasome in the cytosol to protect the organism from pathogens and environmental factors [59]. The results of this study suggest that NLRs may act as sensors to salinity stress, which is in agreement with previous studies in grass carp (Ctenopharyngodon idella) [60]. In particular, the expression of CLRs and NLRs in the GDA and KIEL subpopulations depends on the transcript variant, which is in accordance with our previous study, and indicates that alternative splicing supports the response to the variable salinity environment in Atlantic cod [14].…”
Section: Discussionsupporting
confidence: 91%
“…NLRs play a crucial role in the inflammatory response by forming an inflammasome in the cytosol to protect the organism from pathogens and environmental factors [59]. The results of this study suggest that NLRs may act as sensors to salinity stress, which is in agreement with previous studies in grass carp (Ctenopharyngodon idella) [60]. In particular, the expression of CLRs and NLRs in the GDA and KIEL subpopulations depends on the transcript variant, which is in accordance with our previous study, and indicates that alternative splicing supports the response to the variable salinity environment in Atlantic cod [14].…”
Section: Discussionsupporting
confidence: 91%
“…CA is considered a crucial stress factor as it affects the survival of aquatic animals in saline-alkali water [ 6 ]. Previous studies have shown that carbonate alkalinity could cause a series of problems for aquatic animals, such as respiratory and metabolic alkalosis [ 7 ], tissue oxidative damage [ 8 ], intestinal flora imbalance [ 9 ], as well as disorders of the antioxidant and immune system [ 10 ], which seriously affect the normal growth, development and reproduction of fish. At the same time, recent studies have shown that the extent of freshwater salinization continues to deepen as a result of human activities and global warming, which might steadily shrink the available space for freshwater aquaculture [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because inland waters are more polluted and cyanobacteria blooms frequently occur, silver carp are often exiled into lakes and reservoirs, where they proliferate extensively, to control the abnormal growth of algae and obtain economic benefits [ 22 , 23 ]. Currently, many studies have been conducted on the effects of salinity on freshwater fish [ 24 , 25 , 26 ]. Some freshwater fish have been successfully cultivated in saline–alkali water, including crucian carp ( Carassius auratus gibelio ), grass carp ( Ctenopharyngodon idella ), bighead carp ( Hypophthalmichthys nobilis ), medaka ( Oryzias latipes ), and channel catfish ( Ictalurus punctatus ) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many studies have been conducted on the effects of salinity on freshwater fish [ 24 , 25 , 26 ]. Some freshwater fish have been successfully cultivated in saline–alkali water, including crucian carp ( Carassius auratus gibelio ), grass carp ( Ctenopharyngodon idella ), bighead carp ( Hypophthalmichthys nobilis ), medaka ( Oryzias latipes ), and channel catfish ( Ictalurus punctatus ) [ 26 ]. This not only results in the improved utilization rate of saline–alkali water but is also important economically for the aquaculture of freshwater fish in saline–alkali areas.…”
Section: Introductionmentioning
confidence: 99%